Effect of a patient training video on visual field test reliability. Issue 2 (1st February 2003) - Sherafat, H; Spry, P G D; Waldock, A; Sparrow, J M; Diamond, J P
Abstract : Aims: To evaluate the effect of a visual field test educational video on the reliability of the first automated visual field test of new patients. Methods: A prospective, randomised, controlled trial of an educational video on visual field test reliability of patients referred to the hospital eye service for suspected glaucoma was undertaken. Patients were randomised to either watch an educational video or a control group with no video. The video group was shown a 4.5 minute audiovisual presentation to familiarise them with the various aspects of visual field examination with particular emphasis on sources of unreliability. Reliability was determined using standard criteria of fixation loss rate less than 20%, false positive responses less than 33%, and false negative responses less than 33%. Results: 244 patients were recruited; 112 in the video group and 132 in the control group with no significant between group difference in age, sex, and density of field defects. A significant improvement in reliability (p=0.015) was observed in the group exposed to the video with 85 (75.9%) patients having reliable results compared to 81 (61.4%) in the control group. The difference was not significant for the right (first tested) eye with 93 (83.0%) of the visual fields reliable in the video group compared to 106 (80.0%) in the control group (p = 0.583), but was significant for the left (second tested) eye with 97 (86.6 %) of the video group reliable versus 97 (73.5%) of the control group (p = 0.011). Conclusions: The use of a brief, audiovisual patient information guide on taking the visual field test produced an improvement in patient reliability for individuals tested for the first time. In this trial the use of the video had most of its impact by reducing the number of unreliable fields from the second tested eye.